Systemic versus local adipokine expression differs in a combined obesity and osteoarthritis mouse model - Hülser, Marie Lisa; Luo, Yubin; Frommer, Klaus; Hasseli, Rebecca; Köhler, Kernt; Diller, Magnus; Van Nie, Lina; Rummel, Christoph; Roderfeld, Martin; Roeb, Elke; Schett, Georg; Bozec, Aline; et al. (Scientific Reports, 2021)
Osteoarthritis (OA) is a degenerative joint disease characterized by cartilage loss and reduced joint function. OA risk factors are age and obesity. Many adipokines are altered by obesity but also OA although systemic adipokine regulation in OA is not always clear. Therefore, metabolic effects of diet-induced obesity on OA development as well as the influence of obesity and OA progression on systemic vs. local adipokine expression in joints were compared. C57Bl/6-mice fed with HFD (high fat diet) or normal diet prior to destabilization of the medial meniscus (DMM) were sacrificed 4/6/8 weeks after surgery. Sera were evaluated for adiponectin, leptin, visfatin, cytokines. Liver grading and staging for non-alcoholic steatohepatitis (NASH) was performed and crown-like structures (CLS) in adipose tissue measured. OA progression was scored histologically. Adipokine-expressing cells and types were evaluated by immunohistochemistry. Time-dependent changes in DMM-progression were reflected by increased systemic adiponectin levels in DMM especially combined with HFD. While HFD increased serum leptin, DMM reduced systemic leptin significantly. OA scores correlated with bodyweight, leptin and hepatic scoring. Locally, increased numbers of adiponectin- and leptin-producing fibroblasts were observed in damaged menisci but visfatin was not changed. Local adipokine expression was independent from systemic levels, suggesting different mechanisms of action.
CRIS-Team Scopus Importer:2021-08-27